Penerapan Kelima Nilai Pancasila Dalam Putusan Hakim Di Indonesia - Sujatmiko, Bagus; Muhammad Nurulloh Jarmoko; Syifa Alam (University of Muhammadiyah Malang, 2024)
This research aims to understand the values of Pancasila and apply those values in the drafting of judicial decisions by judges. This study is conducted using a normative juridical method, which is a type of research that analyzes or examines the internal aspects of the prevailing law. Pancasila is the foundation of the State and the ideology that serves as a guide in various aspects of life in Indonesia. As the country's philosophical foundation, Pancasila emphasizes universal values such as justice, unity, democracy, humanity, and belief in Almighty God. A judge's decision is a written document drafted by the judge as a reflection of the judge's intellectual and moral considerations, with the purpose of upholding justice in society. The process of making a judicial decision consists of three main stages: case examination, judges' deliberation, and the formulation of the decision. The values of Pancasila, which include belief in God, humanity, unity, democracy, and social justice, are fundamental to national and state life, including in the drafting of judicial decisions. Judges are obligated to reflect these values in the judicial process to achieve justice that aligns with moral and ethical principles. Judicial decisions must apply the values of Pancasila because Pancasila is the state's ideological foundation, which serves as the philosophical, ethical, and normative basis for national life in Indonesia. As the source of all legal sources, Pancasila imbues the Indonesian legal system, including the judicial process.